2020
DOI: 10.3389/fonc.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

The Menstrual Cycle and Risk of Breast Cancer: A Review

Abstract: Cyclic hormonal stimulation of the breast tissue plays a significant role in breast carcinogenesis. Current risk factor models do not include direct measures of cycle characteristics although the effects of possible surrogates of cycle activity such as age at menarche and menopause, parity, and nursing time have been investigated. Future risk models should also include menstrual cycle length, regularity, number of cycles before first full-term pregnancy, and lifetime number of cycles. New risk factor models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
0
26
0
2
Order By: Relevance
“…Moreover, testosterone use reduces breast tissue density [ 51 ], and dense breast tissue has been shown to be a risk factor for breast malignancy [ 52 ]. Another risk factor for breast malignancy is a high number of menstruation cycles and high lifetime menstruation activity [ 53 ]. Testosterone could have an antiproliferative effect by suppressing the menstruation cycles in FtM transsexuals [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, testosterone use reduces breast tissue density [ 51 ], and dense breast tissue has been shown to be a risk factor for breast malignancy [ 52 ]. Another risk factor for breast malignancy is a high number of menstruation cycles and high lifetime menstruation activity [ 53 ]. Testosterone could have an antiproliferative effect by suppressing the menstruation cycles in FtM transsexuals [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Nipple aspiration fluid (NAF) cytology is considered as predictor for breast cancer [ 23 ], with a high diagnostic specificity (0.97), but a low sensitivity (0.64) which limits diagnostic accuracy [ 24 ]. As hormonal stimulation of the breast tissue plays a considerable role in breast carcinogenesis and for the length of the menstrual cycle (MC), the latter might be relevant for breast cancer risk [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Every month cyclic hormones activate stem cells to begin preparing the endometrium or breast tissue for an eventual pregnancy without this event actually occurring, and a default programme is then invoked to reset the calendar. Besides the accompanying menstruation and/or mental disruption this provokes, it has been also suggested that this activation/reset system is one factor predisposing women to reproductive tissue cancer ( Olsson and Olsson, 2020 ). Second, contraceptive systems have been developed to provide planning for reproduction to coincide with an optimal economic environment.…”
Section: Age and Reproductionmentioning
confidence: 99%